Kin-Avoidance in Cannibalistic Homicide - Oostland, Marlies; Brecht, Michael (Frontiers in Psychology, 2020)
Cannibalism in the animal kingdom is widespread and well characterized, whereas the occurrence of human cannibalism has been controversial. Evidence points to cannibalism in aboriginal societies, prehistory and the closely related chimpanzees. We assembled a non-comprehensive list (121 offenders, ~ 631 victims) of cannibalistic homicides in modern societies (since 1900) through internet-searches, publications and expert questioning. Cannibalistic homicides were exceedingly rare, and often sex-related. Cannibalistic offenders were mainly males and older than offenders of non-cannibalistic homicides, whereas victims were comparatively young. Cannibalistic offenders typically killed manually (stabbing, strangulating, beating) rather than by guns. Furthermore, they killed more strangers and fewer intimates than conventional offenders. Human cannibals, as other cannibalistic species, killed and ate conspecifics, occasionally vomited and only rarely (2.5% of victims) ate kin. Interestingly, cannibalistic offenders who killed their blood relatives had more severe mental problems than non-kin-cannibals. We conclude that cannibalistic homicides have a unique pattern of murder methods, offenders, and victims.